2007
DOI: 10.1534/genetics.107.080788
|View full text |Cite
|
Sign up to set email alerts
|

A Measurable Increase in Oxidative Damage Due to Reduction in Superoxide Detoxification Fails to Shorten the Life Span of Long-Lived Mitochondrial Mutants of Caenorhabditis elegans

Abstract: SOD-1 and SOD-2 detoxify superoxide in the cytoplasm and mitochondria. We find that, although several long-lived mutants of Caenorhabditis elegans have increased SOD levels, this phenomenon does not correlate with life span or growth rate. Furthermore, although disruption of sod-1 or -2 expression produces numerous phenotypes, including increased sensitivity to paraquat and increased oxidative damage to proteins (except in daf-2 mutants), this fails to shorten the life span of these long-lived mutants. In fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
151
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 156 publications
(173 citation statements)
references
References 67 publications
(86 reference statements)
16
151
3
1
Order By: Relevance
“…The isp‐1(qm150) point mutation slows mitochondrial electron transport and increases mitochondrial superoxide generation but not general oxidative stress or sensitivity to loss of superoxide detoxification (Feng et al ., 2001; Yang et al ., 2007; Yang & Hekimi, 2010a). Treatment of isp‐1(qm150) with NAC at the lowest concentration leads to a particularly dramatic increase in lifespan of these already very long‐lived mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The isp‐1(qm150) point mutation slows mitochondrial electron transport and increases mitochondrial superoxide generation but not general oxidative stress or sensitivity to loss of superoxide detoxification (Feng et al ., 2001; Yang et al ., 2007; Yang & Hekimi, 2010a). Treatment of isp‐1(qm150) with NAC at the lowest concentration leads to a particularly dramatic increase in lifespan of these already very long‐lived mutants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we have previously shown that oxidative damage does not cause worm aging because increasing levels of oxidative damage were shown not to impact lifespan (28) and increased oxidative damage was shown to be compatible with long life (22). In future studies, it would be interesting to examine other forms of molecular damage to determine whether these are affected in sod-12345 worms.…”
Section: -G)mentioning
confidence: 96%
“…In this way the mutations also delay the onset of the thresholds that lead to the run-away process and thus to a negative effect of ROS on the aging process. This could explain why both C. elegans and mouse mutants with elevated mitochondrial ROS generation [43,48] have low levels of overall ROS damage [51,58]. Similarly, the hypothesis also provides an explanation for why overexpression of antioxidant proteins or treatment with antioxidant drugs are unable to extend lifespan and rather cause cellular dysfunction [59] (Figure 1).…”
Section: The Gradual Ros Response Hypothesismentioning
confidence: 97%